Ownership and identities of the largest shareholders and dividend policy: Evidence from Vietnam - LE, Trien Vinh (Institutional Knowledge at Singapore Management University, 2017)
This study investigates the relationship between the level of shareholdings and identities of the largest shareholders, and cash dividend policy. The study is conducted with a sample of 180 firms listed on Vietnam stock exchange markets from 2009 to 2013. The fixed effect model is employed to analyze the balanced panel data. The results show that the higher the level of holdings by the largest shareholders, the lower the dividend payout. Moreover, companies with the State and Foreign investors as the largest shareholders have higher dividend payout ratio than companies with local investors and managers as the largest shareholders. The study also finds that companies tend to pay higher dividends when profits decrease or growth opportunities increase.